2020
DOI: 10.1038/s41586-020-2604-2
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-derived metabolite promotes HDAC3 activity in the gut

Abstract: The coevolution of mammalian hosts and their beneficial commensal microbes has led to development of a symbiotic host-microbiota relationship 1 . Epigenetic machinery permits mammalian cells to integrate environmental signals 2 , however, how these pathways are finely tuned by diverse cues from commensal bacteria is not well understood. Here, we reveal a highly selective pathway through which microbiota-derived inositol phosphate regulates histone deacetyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
116
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(130 citation statements)
references
References 43 publications
2
116
1
1
Order By: Relevance
“…As EEN is typically very low in fiber, EEN has been shown to reduce fecal levels of SCFAs such as butyrate [ 114 ]. Butyrate regulates the expression of epigenetic enzymes, notably, histone deacetylases (HDACs) that have a role in controlling the immune response and gut activity [ 115 , 116 ].…”
Section: Potential Mechanisms Of Action Of Nutritional-therapy-indmentioning
confidence: 99%
“…As EEN is typically very low in fiber, EEN has been shown to reduce fecal levels of SCFAs such as butyrate [ 114 ]. Butyrate regulates the expression of epigenetic enzymes, notably, histone deacetylases (HDACs) that have a role in controlling the immune response and gut activity [ 115 , 116 ].…”
Section: Potential Mechanisms Of Action Of Nutritional-therapy-indmentioning
confidence: 99%
“…In addition to canonical microbial sensing pathways, epigenetic mechanisms enable environmental signals to instruct cellular responses and represent another interface by which microbiota can impact mammalian cells (Amatullah and Jeffrey, 2020;Woo and Alenghat, 2017). Consistent with this, epigenetic-modifying enzymes in IECs integrate microbiota-derived signals to regulate intestinal homeostasis and immunity (Ansari et al, 2020;Navabi et al, 2017;Takahashi et al, 2009;Wu et al, 2020). Epigenetic-modifying enzymes mediate covalent chromatin modifications that alter DNA accessibility and gene expression.…”
Section: Introductionmentioning
confidence: 85%
“…In a recent study in Nature, Wu et al discovered a fundamental host-microbe interaction that is crucially involved in responding to dietary change thereby maintaining healthy intestinal dynamics. 1 They demonstrated that HDAC3 activity can be promoted by microbiota-mediated phytate metabolism to contribute intestinal homeostasis and repair.…”
mentioning
confidence: 99%
“…In a recent study of Wu et al, they identified a novel microbiota-mediated metabolic pathway that could activate HDAC to contribute intestinal homeostasis. 1 Butyrate is well-documented for suppressing HDAC activation. 4 Indeed, colonising germ-free (GF) mice with butyrate-producing bacteria (Faecalibacterium prausnitzii) largely inhibited HDAC enzymatic activity in IECs.…”
mentioning
confidence: 99%
See 1 more Smart Citation